The impact of forensic work on home life: the role of emotional labour, segmentation/integration and social support. Issue 1 (8th February 2016) - Johnson, Helen; Worthington, Rachel; Gredecki, Neil; Wilks-Riley, Fiona Rachel
Abstract : Purpose: – Adopting a person-environment (P-E) fit approach, the purpose of this paper is to examine the role of emotional labour, segmentation/integration and social support in the development of work-home conflict. Design/methodology/approach: – Mental health professionals ( n =118) completed the work-home conflict and home-work conflict scales (Netemeyer et al., 1996), the segmentation preferences and supplies scales (Kreiner, 2006) and the Mann Emotion Requirements Inventory (Mann, 1999). A social support checklist was also developed to assess the perceived value of work and non-work sources of support. Findings: – Contrary to expectation, emotional labour was associated with lower levels of work-home conflict. There was no evidence found for the relevance of a P-E fit approach, rather the results indicated that the perception that the organisation supports the separation of work and home is sufficient in ameliorating work-home conflict. In addition, work-based support was found to reduce work-home conflict. Research limitations/implications: – The importance of support within the work environment as a way of reducing work-home conflict has been highlighted. That is, providing a safe environment to discuss anxieties and concerns is a fundamental factor when developing organisational support structure. The importance of providing professionals with choice regarding their preference to segment or integrate work and home has also been highlighted. Based on the contradictory findings with regards to emotional labour and work-home conflict, future research should aim to further examine this relationship within a forensic psychiatric setting. Originality/value: – This is the first research paper to explore the role of emotional labour, segmentation/integration and social support in the development of work-home conflict.